Pengembangan Video Pembelajaran PBL Berbasis Google Site untuk Peningkatan Representasi Matematis dan Berpikir Kritis Materi Gelombang Cahaya - Rifkiyatul Khairiyah; Sukardiyono Sukardiyono; Yusman Wiyatmo; Kuncoro Asih Nugroho; Riki Perdana; Ahmad Irdinansyah (Media Pendidikan Matematika, 2025)
This study aims to develop a problem–based learning video delivered through Google Sites on the topic of light waves and to examine its practicality and effectiveness in improving students’ mathematical representation and critical thinking skills. The research employed a Research and Development (R&D) approach using the ADDIE model, from analysis to evaluation. Feasibility assessments were conducted by physics lecturers and teachers, while field implementation involved students of MAN 3 Sleman in the 2024/2025 academic year, selected through cluster random sampling. Research instruments consisted of pretest–posttest assessments and questionnaires, and data analysis included expert validation, students’ responses, and multivariate effectiveness testing. The results indicate that the developed instructional video is feasible, practical, and effective in enhancing mathematical representation and critical thinking skills. The novelty of this study lies in integrating problem–based learning into an interactive video format organized within a structured Google Sites ecosystem. Practically, the product enables teachers to use the video as a problem-triggering medium and as support for students’ independent learning processes.